2008
DOI: 10.1111/j.1471-0528.2008.01727.x
|View full text |Cite
|
Sign up to set email alerts
|

Does self‐administered vaginal misoprostol result in cervical ripening in postmenopausal women after 14 days of pre‐treatment with estradiol? Trial protocol for a randomised, placebo‐controlled sequential trial*

Abstract: Objective To compare the impact of 1000 micrograms of selfadministered vaginal misoprostol versus self-administered vaginal placebo on preoperative cervical ripening after pre-treatment with estradiol vaginal tablets at home in postmenopausal women prior to day-care operative hysteroscopy.Design Randomised double-blind placebo-controlled sequential trial. The boundaries for the sequential trial were calculated on the primary outcomes of a difference of cervical dilatation ‡1 millimetre, with the assumption of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…In the current study, 200 and 400 μg misoprostol significantly shortened the dilatation time (20. 19 In the present study, it was shown that the misoprostol effect was similar in both premenopausal and postmenopausal women. This finding is similar to the results of a study performed by Gkrozou et al, which mentioned that vaginal misoprostol decreased the requirement for cervical dilatation in both premenopausal and postmenopausal patients (18).…”
Section: Discussionsupporting
confidence: 58%
“…In the current study, 200 and 400 μg misoprostol significantly shortened the dilatation time (20. 19 In the present study, it was shown that the misoprostol effect was similar in both premenopausal and postmenopausal women. This finding is similar to the results of a study performed by Gkrozou et al, which mentioned that vaginal misoprostol decreased the requirement for cervical dilatation in both premenopausal and postmenopausal patients (18).…”
Section: Discussionsupporting
confidence: 58%
“…We refer to the previously published trial protocol for comprehensive methodological details 24. Those eligible for the study were all postmenopausal women (defined as at least 1 year after the last menstrual period/menstruation) referred consecutively for day-care operative hysteroscopy, and who had provided informed written consent.…”
Section: Methodsmentioning
confidence: 99%
“…07/12515-8) for the study. The trial is registered with ClinicalTrials.gov, number NCT00572819, the European Clinical Trials Database, number 2007-004083-52, and the study protocol has been published in BJOG 24. Written informed consent was obtained from all patients before randomisation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation